2010
DOI: 10.2527/jas.2008-1768
|View full text |Cite
|
Sign up to set email alerts
|

Reduced feed intake of lactating primiparous sows is associated with increased insulin resistance during the peripartum period and is not modified through supplementation with dietary tryptophan1

Abstract: The aim of this experiment was to investigate whether insulin resistance is related to the dietary concentration of Trp and the ADFI of primiparous sows having similar body conditions. Twenty-four primiparous sows were catheterized on d 97 of pregnancy. Blood samples were collected during 3 tests: after the ingestion of 1.5 kg of feed (meal test), after the intravenous infusion of 0.5 g of glucose/kg of BW (glucose tolerance test), and during an euglycemic hyperinsulinemic clamp with an infusion rate of 100 ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 24 publications
7
19
0
Order By: Relevance
“…In this regard, some studies have demonstrated that the feed intake of sows during lactation is negatively related to the insulin‐resistance during the periparturient period (Mosnier et al. ), moreover, in the present study, the sows fed HMB diet had higher fasting plasma glucose content than sows fed the control diet at days 2 and 28 of lactation (Table ), which provided further evidence for the increased insulin resistance. Therefore, the reduced feed intake of sows during lactation in the HMB group might be associated with the increased insulin resistance, and the underlying mechanism of which remains to be elucidated further.…”
Section: Discussionsupporting
confidence: 74%
“…In this regard, some studies have demonstrated that the feed intake of sows during lactation is negatively related to the insulin‐resistance during the periparturient period (Mosnier et al. ), moreover, in the present study, the sows fed HMB diet had higher fasting plasma glucose content than sows fed the control diet at days 2 and 28 of lactation (Table ), which provided further evidence for the increased insulin resistance. Therefore, the reduced feed intake of sows during lactation in the HMB group might be associated with the increased insulin resistance, and the underlying mechanism of which remains to be elucidated further.…”
Section: Discussionsupporting
confidence: 74%
“…The daily food intake of rat pups measured between Day 39 and Day-42 showed that the food consumption of the LP group is lower than the CP group irrespectively of a supplementation by L-tryptophan (Figure S1) . These observations on nursing rats with offspring are similar to results obtained in lactating sows [16]. In addition, the relative food intake was higher for the LP group during the night cycle but the relative intakes of both groups were similar during the light cycle ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 85%
“…From human studies, we also know that the circadian rhythm of tryptophan in breast milk affects the rhythms of 6-sulfatoxymelatonin and sleep in newborn [12], [13] and that infant formulas supplemented in L-tryptophan during the night can alter the expression of genes in cerebellum of nursing rat neonates [14]. It has been found that acute supplementation with tryptophan show transitory increase of melatonin plasma levels [15] as well as alteration in insulin secretion [16].…”
Section: Introductionmentioning
confidence: 99%
“…The transition from gestation to lactation is characterized by physiological and metabolic changes, such as a progressive decrease in insulin sensitivity during late gestation and lactation (Pere et al, 2000;Pere and Etienne, 2007). During lactation, insulin resistance is negatively correlated with the feed intake of sows (Van der Peet-Schwering et al, 2004;Mosnier et al, 2010). Several studies have shown that soluble dietary fiber can improve insulin sensitivity in mice or rats (Song et al, 2000;Isken et al, 2010).…”
Section: Discussionmentioning
confidence: 99%